Meta-Analysis Study: The Effect of Augmented Reality on Student Learning Outcomes - Laksmi Evasufi Widi Fajari; Popi Dayurni; Ayu Rahayu (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This study aims to determine the effect of Augmented Reality on student learning outcomes. This study consists of two variables: Augmented Reality as the independent variable and student learning outcomes as the dependent variable using quantitative meta-analysis research. The instrument used is an article coding sheet containing the data needed for meta-analysis in the form of mean data, the number of samples, and the standard deviation of control and experimental groups from articles that have passed the selection based on inclusion and exclusion criteria obtained through Google Scholar search. The results of the meta-analysis on 13 research articles obtained a summary effect (average effect size) of 0.541 which means that augmented Reality has a significant positive effect on student learning outcomes based on the effect size category set by Cohen. The results of the publication bias test show that the conclusion of the meta-analysis is not indicated by publication bias, as evidenced by the results of the funnel plot, egger test, and fail-safe N results. This study concludes that there is an effect of Augmented Reality on student learning outcomes.